PENGEMBANGAN PROTOTYPE APLIKASI NOTIFIKASI JADWAL UJIAN BERBASIS ANDROID - Bambang Ismanto; Dicke Junryan Saut HS; Nurul Amalia (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
Examination is one of the academic activities carried out to test students in mastery of competence in the subjects studied in one semester. This exam is mandatory for students to take because it is related to the student's grades and graduation in the course. In carrying out the exam, students must remember the schedule so that they can take the exam according to the schedule given. From the results of the initial questionnaire distributed to 18 students, it was found that 3 or 16% of students had taken the exam according to the specified schedule. This happens because students forget the schedule that has been recorded or students do not record the schedule given. The use of android applications as time reminders can be used to overcome these problems. The application was developed using the prototype method with the stages of communication, planning, modeling, construction and evaluation. This study was conducted to determine the benefits of using Android-based learning schedule notifications for STMIK Widya Pratama Pekalongan students. From the research carried out, it was found that the use of this exam time application can make it easier for students to save exam schedules that can be seen when needed and can make it easier for students to remember the exam schedule by displaying notifications on Android devices 1 day before the exam is held.